Cortical and subcortical signatures of conscious object recognition - Max Levinson (Nature Portfolio, 2021)
Cortical and subcortical neural activity supporting conscious object recognition has not yet been well defined. Here, the authors describe these networks and show recognition-related category information can be decoded from widespread cortical activity but not subcortical activity.